ANALYSIS OF TOTAL QUALITY MANAGEMENT (TQM) STRATEGY IN ISLAMIC EDUCATION MANAGEMENT - Purwanti, Purwanti; Hadinata, Febryan; Fitriyanti, Fitriyanti; Zikri, Zikri; Sirait, Abdullah; Asrori, Achmad (Waniambey: Journal of Islamic Education, 2024)
The implementation of Total Quality Management (TQM) in Islamic educational institutions is a challenge in an effort to improve the quality of education sustainably. This study aims to analyse the impact of TQM implementation on improving the quality of education, focusing on changes in student exam results, parental satisfaction, and student and staff engagement. The research method used is Systematic Literature Review (SLR), which analyses various relevant academic sources, such as international journals, scientific articles, and books related to TQM in Islamic education in the last five years. The data obtained showed that the implementation of TQM had a positive impact, with a 15% increase in student exam results, 85% of parents were satisfied with teaching and administration, and 90% of students were satisfied with the quality of teaching and extracurricular activities. In addition, 80% of staff felt more involved in the process of improving the quality of education. In conclusion, the implementation of TQM proved effective in improving the quality of education in Islamic educational institutions, creating a more qualified, productive and sustainable environment.